LAND TENURE SYSTEM DALAM MELINDUNGI LAHAN PERTANIAN PANGAN BERKELANJUTAN DAN KEDUDUKANNYA DALAM HUKUM AGRARIA NASIONAL - Anita Kamilah; Yuyun Yulianah (Universitas Suryakancana, 2016)
By the increasing of the population and the economic structural development, the need of land for non-agricultural activities are likely to rise. This phenomenon leads a conversion of agricultural land, especially the unavoidable paddy. The causative factors of agricultural land conversion are: (1) Population; (2) The need of non-agricultural soil; (3) Economy; (4) Socio-cultural; (5) Autonomous Region; and (6) Lack of regulation. The Impacts of this conversion not only threatening food security but also interfering the stability of the economy, social, political, and development of the general population. There are three ways in controlling the use of land, they are: (1) Regulation; (2) Acquisition and management, those are perfecting the system and rules of land selling and the perfection of land tenure patterns (Land Tenure system) in supporting efforts towards maintaining agricultural land; and (3) Incentive and charges.Keywords: Agricultural land conversion, Food Security, Land Tenure System